Behold Your Mother: The Experience of a Contemporary Martyr, Chrisophe Lebreton (1950-1996) - Olivera, Bernardo (Cistercian studies quarterly, 2006)
The article features the life and works of the Cistercian monk Christophe Lebreton who was murdered on May 21, 1996. Lebreton was born on October 11, 1950 in Blois, France, and started his religious formation at the Cistercian monastery in Our Lady of Atlas in Algeria. He was known within his community for his poetic works expressing a Marian theological view. His writing depicts testimonial love for God and his total consecration to Jesus' mother Mary.